Facile and multiple replication of superhydrophilic-superhydrophobic patterns using adhesive tape - Auad, Priscila; Boles, Erica Ann; Levkin, Pavel (ACS applied materials & interfaces, 2013)
Surfaces patterned with both hydrophilic and hydrophobic regions are useful in a variety of applications. For example, they can be used as surface tension-confined microchannels, in paper-based microfluidics, or for patterning cells. To create a new patterned substrate, usually the entire experimental procedure must be repeated, which can be time-consuming and laborious. In this paper, we present a simple and fast method that allows the transfer of superhydrophilic-superhydrophobic micropatterns in porous polymer films onto adhesive tape. Replicating patterns using adhesive tape is economical, as the fabrication of one patterned substrate can be used to create multiple copies of the micropatterns, which can then be used for several different experiments. We demonstrate that at least twelve consecutive copies can be made from 125 μm-thick patterned polymer films. Since the polymer film is transferred to adhesive tape, which is flexible, the copies can be used on curved surfaces and they can also be cut into different shapes and sizes. We also demonstrate an application of the replicated patterned polymer surfaces as a substrate for reverse cell transfection experiments.